Public Opinions on Prostitution, Venereal Diseases and AIDS, Paseechareon District, Bangkok - Suterawut, La-iat; Kalong, Vilasinee (Journal of Health Science of Thailand, 1995)
The objective of this study is to assess the public opinion on prostitution, STD and AIDS among various groups of population in Paseechareon District, Bangkok. The study was done by interviewing samples randomly selected from 6 different profession: district officers, sub district and village headmen, teachers, bank workers, policemen and entertainment businessmen. It was found that the respondents were all aware of problems of prostitution and its related undesirable consequences such as the rapid spread of AIDS and the bad reputation for having a very high number of sex workers in all regions of the country. These problems could be possibly controlled by enforcing the Prostitution Act and placing stronger punishment to those who offended the law. However, since it became a norm for men to buy sex services from prostitutes who engaged in the sex business because of such underlying conditions as poverty and low education, the regular and proper use of condoms would be an effective means to urgently prevent STD and AIDS in Thailand.